2021
DOI: 10.1097/md.0000000000026551
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of m6A regulators’ prognostic significance for endometrial cancer

Abstract: Background: Endometrial cancer (EC) is the sixth most common cancer in women globally. It has been found that the expression levels of m6A regulators can be potentially used for prognostic stratification in some cancers, but the role of m6A regulators in EC prognosis remains unclear. Methods: The data of 584 EC samples were downloaded from The Cancer Genome Atlas and the mRNA expression profiles of 20 m6A regulators were analyzed, followed by functional enrichment analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…IRS1 plays a key role in cancer cell proliferation and mediates the resistance to anticancer drugs [90]. IGF2BP1 expression increased in EC, and high expression of this protein correlated with poor prognosis [91]. IGF2BP1 overexpression can promote cell proliferation and regulate the tumor cell cycle and cancer progression, both in vivo and in vitro.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…IRS1 plays a key role in cancer cell proliferation and mediates the resistance to anticancer drugs [90]. IGF2BP1 expression increased in EC, and high expression of this protein correlated with poor prognosis [91]. IGF2BP1 overexpression can promote cell proliferation and regulate the tumor cell cycle and cancer progression, both in vivo and in vitro.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…For example, METTL3, ZC3H13, YTHDC1, and YTHDF1 have been found to be prognostic markers of cervical cancer (84). IGF2BP3, KIAA1429, IGF2BP1, YTHDF3, ZC3H13, YTHDC1, and METTL14 can be used as prognostic markers of endometrial cancer (93,94). HNRNPA2B1, KIAA1429, and WTAP can be used as prognostic markers of ovarian cancer (114).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, IGF2BP3, KIAA1429, and IGF2BP1 can effectively predict the prognosis of patients (93). In addition, Pang et al found that IGF2BP1 and YTHDF3 had a strong ability to stratify the prognosis of different endometrial cancer patients (94). Song et al downloaded the human endometrial carcinoma m 6 A sequencing dataset "GSE93911" from the comprehensive gene expression database.…”
Section: Prognostic Effect Of M 6 a Rna Methylation Regulators On End...mentioning
confidence: 99%
“…It is well known that abnormal ferroptosis is an important reason behind the poor prognosis of endometrial cancer, as indicated by the evidence that molecular typing based on ferroptosis-associated genes showed good prognosis predictive value: 1) the ferroptosis score, based on thirteen ferroptosis-associated genes, was established, and OS of patients with a low score of ferroptosis was superior to that of those with high score of ferroptosis (AUC = 0.726) (Wang et al, 2021b); 2) a molecular typing of endometrial cancer, based on six ferroptosisassociated genes of HMOX1, KEAP1, HSBP1, SAT1, CISD1, and GPX4, showed good 1-, 3-, and 5-year prognostic predictive value (AUC = 0.705, 0.676, and 0.713) (Liu J. et al, 2021); 3) a ferroptosis-associated gene signature with eight genes of MDM2, GPX4, PRKAA2, PRNP, SLC11A2, ATP5MC3, PHKG2, and ACO1, showed better 1-, 3-, and 5-year prognostic predictive value (AUC = 0.676, 0.797, and 0.826) than the aforementioned two ferroptosis prognosis molecular typings (Weijiao et al, 2021). Ferroptosis prognosis molecular typing possessed a comparable or superior prognosis predictive value when compared with the previous prognosis molecular typings of endometrial cancer (Table 1) (Tang et al, 2019;Yang et al, 2021b;Coll-de la Rubia et al, 2021;Huang S. et al, 2021;Lu N. et al, 2021;Pang et al, 2021;Wang Z. et al, 2021). As indicated by the evidence, ferroptosis-associated genes-based molecular typing can be considered as an effective method to predict the prognosis of endometrial cancer.…”
Section: Ferroptosis and Prognosis Of Endometrial Cancermentioning
confidence: 93%